2005
DOI: 10.1128/aem.71.12.7750-7758.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Tropospheric Ozone on the Structure of Bacterial Communities Inhabiting the Rhizosphere of Herbaceous Plants Native to Germany

Abstract: Current elevated concentrations of ozone in the atmosphere, as they are observed during summer seasons, can cause severe effects on plant vegetation. This study was initiated to analyze whether ozone-stressed plants also transfer signals below ground and thereby alter the bacterial community composition in their rhizospheres. Herbaceous plants, native to Germany, with tolerance (Anthoxanthum odoratum, Achillea millefolium, Poa pratensis, Rumex acetosa, and Veronica chamaedrys) and sensitivity (Matricaria chamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…This result indicated that fungi are possibly more responsive in the soil of O 3 -stressed early-successional tree species than are bacteria. This minor effect of O 3 on bacteria was corroborated by a study of the bacterial community inhabiting the rhizospheres of herbaceous plants after exposure to eO 3 , which the authors considered to have a surprisingly small effect on the structural diversity of the bacterial community (Dohrmann and Tebbe, 2005). In that study, genetic profiling based on single-strand conformation polymorphisms (SSCP) revealed that the different SSCP profiles generated from the bacterial community of the rhizospheres from O 3 -stressed and control plants were very similar and were not distinguished by statistical methods, which indicated that elevated levels of O 3 did not select for a different bacterial community composition.…”
Section: Shannon-weinner Diversity Richnessmentioning
confidence: 84%
See 1 more Smart Citation
“…This result indicated that fungi are possibly more responsive in the soil of O 3 -stressed early-successional tree species than are bacteria. This minor effect of O 3 on bacteria was corroborated by a study of the bacterial community inhabiting the rhizospheres of herbaceous plants after exposure to eO 3 , which the authors considered to have a surprisingly small effect on the structural diversity of the bacterial community (Dohrmann and Tebbe, 2005). In that study, genetic profiling based on single-strand conformation polymorphisms (SSCP) revealed that the different SSCP profiles generated from the bacterial community of the rhizospheres from O 3 -stressed and control plants were very similar and were not distinguished by statistical methods, which indicated that elevated levels of O 3 did not select for a different bacterial community composition.…”
Section: Shannon-weinner Diversity Richnessmentioning
confidence: 84%
“…Among previous examinations of soil microbial communities, very few have considered rhizosphere soil microbial responses to O 3 . The rhizosphere is the microbial habitat in the soil that is most strongly influenced by plants (Dohrmann and Tebbe, 2005). In several studies, the composition of root exudates, which mainly serve as C and energy sources for soil microorganisms (especially rhizosphere microbes), has been shown to strongly influence the structural and functional diversity of the microbial community (Kowalchuk et al, 2002;Miethling et al, 2000;Schmalenberger and Tebbe, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological analyses of Telluria reveal many features that are consistent with traditional copiotrophic rhizosphere bacteria (Spiegel et al, 1991;Bowman et al, 1993;Anzai et al, 2000). Bacteria from the family Oxalobacteraceae, previously detected in root environments (Hallmann et al, 1997;Mahaffee and Kloepper, 1997a, b;Olsson et al, 1999;McSpadden-Gardner and Weller, 2001;Johansen and Binnerup, 2002;Schmalenberger and Tebbe, 2002;Graff and Conrad, 2005), have increasingly been seen as important components of rhizosphere communities and have been specifically targeted in rhizosphere studies (Dohrmann and Tebbe, 2005). Unlike the Oxalobacteraceae, the community composition of compost-derived Chryseobacterium was not sensitive to the seed or root environment.…”
Section: Seed and Root-colonizing Bacteria Sj Green Et Almentioning
confidence: 87%
“…The identification of DNA sequences recovered from bands of SSCP profiles followed the protocol described elsewhere, with three clones selected to identify each band of interest (Dohrmann and Tebbe, 2005).…”
Section: Cloning Of Pcr Products and Dna Sequence Analysesmentioning
confidence: 99%